Improving the Escalation of Micro, Small, and Medium Enterprises (MSME) Based on Digital Economy Acceleration and Capability Through Value Creation on West Java SME Enterpriser - Hermina, Nurul (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
MSME acceleration in Indonesia has an essential role in enhancing the national economy and contributing significantly to Indonesia's GDP. However, in its implementation, there are still several obstacles, including limited connections to digital technology, digital skills, and management. This research investigates the influence of the digital economy and capabilities on business performance through value creation on West Java MSME business actors or enterprises. The research implemented quantitative methods through descriptive and verification analysis, with partial least squares-structural equation modeling (PLS-SEM) analysis techniques. The number of samples used was 127 respondents consisting of experts and practitioners (expert judgment). The sampling technique uses the online sampling method. The research results show that digital economic variables have a significant positive influence on MSME value creation, capability variables hold a direct positive influence on value creation, and also direct and indirect influences on MSME business performance. Value creation variables have a direct influence on business performance. The results of this research can be used to improve digital business in a way that is more appropriate for West Java MSME business actors.